Analytical Study of Contemporary Banking in Islamic pespectiver - manan, Dr. Abdul; Akram, Hassan; -ur-Rehman, Khalil (International Research Journal of Arabic and Islamic Studies, 2022)
Banks have a significant and pivotal role in present global economic system. Bank plays the role of financial intermediary and provides financial services to society. Conventional Banking is based on the common practice of lending money on a fixed and very high rate of interest. This study highlights the concept of interest based banking system and its harmful implications to society. Interest is clearly prohibited as per instructions of Quran and last prophet Hazrat Muhammad (SAW). Since the banking interest is “RIBA”, therefore, it is completely prohibited in Islam. This research study illustrates that interest is strictly prohibited in Islam and it must be banned in banking system by State of Pakistan as per directives of Federal Shariat Court. Further, this study also elaborates how Islamic banking system is showing robust growth around the globe which makes it a complete solution and replacement of conventional interest based banking system not only for Muslims but also for present global financial system crises. Dr. Saqib`s “Akhuwat” is playing a leading role to introduce Islamic banking without interest at global level. Constructive and positive role of “Akhuwat” is commendable. In this article, Contemporary banking system has been analyzed in the light of Islamic teachings.